Spin in particle physics - Leader, Elliot (Cambridge University Press, 2001)
This book will be of value to graduate students and researchers in all areas of quantum physics, particularly in elementary particle and high energy physics. It is suitable as a supplementary text for graduate courses in theoretical and experimental particle physics.